The genus Ophelina Örsted, 1843 (Annelida: Opheliidae) in the coast of Kuwait (northern Indian Ocean), with the description of a new species - Parapar, Julio; Al-Kandari, Manal; Barroso, María; Moreira, Juan (European Journal of Taxonomy, 2023)
Two species of the genus Ophelina Örsted, 1843 (Annelida, Opheliidae) are reported from the coast of Kuwait (Arabian Gulf) after specimens collected in the intertidal and shallow subtidal, namely Ophelina arabica sp. nov. and Ophelina grandis (Pillai, 1961). The new species is mainly characterised by features of the anal tube, which is provided with about 25 annulations at each side; the ventral margins are fully fused while dorsal margins are fused at most of their length but are free at the distal end in the shape of a conspicuous incision; the posterior end is opened with free margins; the anal tube also lacks marginal papillae but bears a pair of basal papillae and an unpaired anal cirrus attached to ventral margin at mid-length. Ophelina grandis is reported for the first time in the Arabian Gulf; specimens are fully described and compared with similar species. A key for species of Ophelina in the Indo-Pacific, Southern Asia, Indo-Malay Archipelago and Australia, is also provided.